Exploring the Impact of Field-Based Learning on Report Writing Skills in Management Classes: A Comprehensive Analysis - Widhi Pratiwi, Dyah Ayu; Sudiran, Sudiran; Hartono, Hartono (Universitas Hamzanwadi, 2023)
This study investigates the efficacy of field studies as a pedagogical tool to enhance report writing skills in management students, who often encounter challenges such as idea generation, sentence construction, thought organization, and low motivation during the writing process. The research primarily aims to analyze the implementation and effectiveness of field studies in teaching report writing, proposing solutions to bolster writing skills and motivation among management students. A qualitative descriptive methodology was employed, involving 25 second-semester management students and an English Language lecturer as participants. The sample was selected through purposive sampling. Data collection comprised observations and interviews, analyzed using Miles and Huberman's qualitative analysis framework, which includes data reduction, data presentation, and a process for drawing conclusions and verification. The findings reveal that field studies in report writing, as implemented at Widyagama Lumajang, utilize a structured approach comprising pre-teaching, teaching, and post-teaching stages. Notable benefits include fostering idea development from real-world experiences, enhancing research and academic writing skills, and boosting critical thinking and student motivation. This approach provides a dynamic learning environment that is both relevant and engaging. Consequently, this research contributes to a deeper understanding of the application and advantages of field studies in teaching report writing in Management. It offers insights into effective strategies to address the common challenges faced by students in developing their writing skills.